Influence of water depth on energy expenditure during aquatic walking in people post stroke. (11th May 2018) - Lim, Hyosok; Azurdia, Daniel; Jeng, Brenda; Jung, Taeyou
Abstract: Background and Purpose: This study aimed to investigate the metabolic cost during aquatic walking at various depths in people post stroke. The secondary purpose was to examine the differences in metabolic cost between aquatic walking and land walking among individuals post stroke. Design: A cross‐sectional research design is used. Methods: Twelve participants post stroke (aged 55.5 ± 13.3 years) completed 6 min of walking in 4 different conditions: chest‐depth, waist‐depth, and thigh‐depth water, and land. Data were collected on 4 separate visits with at least 48 hr in between. On the first visit, all participants were asked to walk in chest‐depth water at their fastest speed. The walking speed was used as a reference speed, which was applied to the remaining 3 walking conditions. The order of remaining walking conditions was randomized. Energy expenditure (EE), oxygen consumption (VO2 ), and minute ventilation (VE ) were measured with a telemetric metabolic system. Results: Our findings showed statistically significant differences in EE, VO2, and VE among the 4 different walking conditions: chest‐depth, waist‐depth, and thigh‐depth water, and land (all p < .05). The participants demonstrated reduction in all variables as the water depth increased from thigh depth to chest depth. Significantly higher values in EE and VO2 were found when the water depth increased from waist depth to chest depth. However, no significant difference was found in all variables between thigh‐depth and waist‐depth walking. Only thigh‐depth walking revealed significant differences when compared with land walking in all variables. Conclusions: People post stroke consume less energy in chest‐depth water, which may allow them to perform prolonged duration of training. Thigh‐depth water demonstrated greater EE compared with other water depths; thus, it can be recommended for time‐efficient cardiovascular exercise. Waist‐depth water showed similar EE to land walking, which may have been contributed by the countervailing effects of buoyancy and water resistance.